Gambaran Patologi Bursa Fabricius Embrio Ayam Pascavaksinasi Gumboro Secara In Ovo Menggunakan Vaksin Lokal dan Komersial (PATHOLOGIC DESCRIPTION OF BURSA FABRICIUS CHICKEN EMBYROS AFTER IN OVO VACCINATED WITH LOCAL AND COMMERSIAL GUMBORO VACCINES) - Wahyuwardani, Sutiastuti; Priyono, Dewi Ratih Agung; Manalu, Wasmen (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
Bursa Fabricius is a target organ of gumboro virus infection which is often damaged after vaccinationusing hot intermediate gumboro live vaccine. The purpose of this study was to assess pathologic effect oflocal and commercial gumboro vaccines . As many as 45 embryo chicken eggs at nine day old were used inthis research, then grouped into three groups of 15 embryos chicken eggs each, these were: Embryo chickeneggs without vaccination (Group I), vaccinated with IBD intermediate plus commercial vaccine (Group II)and IBD intermediate plus local vaccine (Group III). Vaccinations were done at 14 days old. All groups thenterminated each three embryos at 12 hours, 1, 2, 3 days post vaccination. The results showed that pathologicanatomic lesions could not be detected. Whereas pathologic lesions were detected in the group that werevaccinated with intermediate plus local IBD observed more severe than in the group that vaccinated withintermediate plus commercial IBD. Lesions such as edema, hemorrhages, necrosis of lymphoid cells wereobserved microscopically in embryo at 12 hours, 1, 2 and 3 days post vaccination in Group II and group III.The lesions were more severe at two days post vaccination causing some lymphoid follicles disappeared at three days post vaccination. However, they were not detected again in the bursa Fabricius three days afterhatching. Cells containing antigens of gumboro were detected in the bursa Fabricius of chicken embryo atone day until three days post vaccination, then disappeared after three days post hatch. It was concludedthat pathologic description of bursa fabricius showed that virus vaccines used for vaccinated IBD in ovowere still virulent, that can cause histopathologic lesions. The viruses are suggested to be more attenuatedbefore using as vaccine in ovo.
Keywords: pathologic effect, bursa fabricius, embryonated chicken egg, gumboro, in ovo vaccination